Caring for Critically Ill Patients: Clinicians’ Empathy Promotes Job Satisfaction and Does Not Predict Moral Distress - Lamiani, Giulia; Dordoni, Paola; Vegni, Elena; Barajon, Isabella (Frontiers in Psychology, 2020)
Background. Several studies have highlighted the benefits of empathy in healthcare settings. A correlation between clinicians’ empathy and patients’ adherence and satisfaction, as well as the ability for the clinician to accurately assess family members' needs, has been found. However, empathy is often seen by clinicians as a risk factor for their wellbeing. This study aims to assess whether the level of empathy of clinicians working in critical care settings may expose them to moral distress, poor job satisfaction, and intention to quit their job. Method. Italian clinicians who attended the 2016 “Smart Meeting Anaesthesia Resuscitation in Intensive Care” completed the Empathy Quotient questionnaire, the Moral Distress Scale-Revised and two questions assessing job satisfaction and intention to quit the job. Multiple linear and logistic regressions were performed to determine if clinicians’ empathy influences moral distress, job satisfaction and intention to quit. Age, gender and profession were used as control variables. Results. Out of 927 questionnaires distributed, 216 were returned (23% response rate) and 210 were used in the analyses. Respondents were 56% physicians, 24% nurses and 20% residents. Over half of the clinicians (58%) were female. Empathy resulted the only significant predictor of job satisfaction (β= .193; p<.05). None of the variables included in the model predicted moral distress. Conclusions. Empathy determined neither moral distress nor intention to quit. Findings suggest that empathy is not a risk factor for critical care clinicians in developing moral distress and the intention to quit their job. On the contrary, empathy was found to enhance clinicians’ job satisfaction.